2017
DOI: 10.1002/smi.2759
|View full text |Cite
|
Sign up to set email alerts
|

Exploring daily affective changes in university students with a mindful positive reappraisal intervention: A daily diary randomized controlled trial

Abstract: Brief and cost-effective interventions focused on emotion regulation techniques can buffer against stress and foster positive functioning. Mindfulness and positive reappraisal are two techniques that can mutually enhance one another to promote well-being. However, research testing the effectiveness of interventions combining mindfulness and reappraisal is lacking. The current pilot examined the effect of a combined mindful-reappraisal intervention on daily affect in a 5-day diary study with 106 university stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 71 publications
2
27
0
Order By: Relevance
“…Mindfulness is used in conjunction with emotion regulation as a mindful state of consciousness that facilitates the awareness and observation of emotions without judgement (Brown, Ryan, & Creswell, ; Glomb, Duffy, Bono, & Yang, ; Reb, Narayanan, & Ho, ). Past research has demonstrated a relationship between mindfulness and emotion regulation in workplace settings (Hülsheger, Alberts, Feinholdt, & Lang, ) and a mindful emotion regulation intervention decreased negative affect in university students (Pogrebtsova, Craig, Chris, O'Shea, & González‐Morales, ).…”
Section: Proactive Behaviour During Economic Recessionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mindfulness is used in conjunction with emotion regulation as a mindful state of consciousness that facilitates the awareness and observation of emotions without judgement (Brown, Ryan, & Creswell, ; Glomb, Duffy, Bono, & Yang, ; Reb, Narayanan, & Ho, ). Past research has demonstrated a relationship between mindfulness and emotion regulation in workplace settings (Hülsheger, Alberts, Feinholdt, & Lang, ) and a mindful emotion regulation intervention decreased negative affect in university students (Pogrebtsova, Craig, Chris, O'Shea, & González‐Morales, ).…”
Section: Proactive Behaviour During Economic Recessionmentioning
confidence: 99%
“…Mindfulness is used in conjunction with emotion regulation as a mindful state of consciousness that facilitates the awareness and observation of emotions without judgement (Brown, Ryan, & Creswell, 2007;Glomb, Duffy, Bono, & Yang, 2011;Reb, Narayanan, & Ho, 2013). Past research has demonstrated a relationship between mindfulness and emotion regulation in workplace settings (Hülsheger, Alberts, Feinholdt, & Lang, 2013) and a mindful emotion regulation intervention decreased negative affect in university students (Pogrebtsova, Craig, Chris, O'Shea, & González-Morales, 2018). Chambers et al's (2009) model of mindful emotion regulation (MER) suggests that it involves a systematic retraining of awareness and non-reactivity, allowing the individual to consciously choose the thoughts and emotions they want to identify with, rather than habitually reacting to them.…”
Section: Mindful Emotion Regulation (Mer) Interventionmentioning
confidence: 99%
“…We therefore posit that exercises which combine mindfulness and positive activities can lead to openness for experiences, positive emotions, and thereby can broaden thought‐action repertoires, as hypothesized in broaden‐and‐build theory (Fredrickson, 2001). In line with this, a study by Pogrebtsova, Craig, Chris, O’Shea, and González‐Morales (2018) found that a mindfulness intervention or combined mindfulness with emotion reappraisal intervention in students led to growth in positive affect and decline in negative affect over the course of 5 days.…”
Section: Introductionmentioning
confidence: 67%
“…One aspect that is examined in positive psychology is how happiness can be pursued and increased (Seligman et al, 2005). Emerging research has provided preliminary support for combining mindfulness and positive activities (Molina & O’Shea, 2020; Pogrebtsova et al, 2018). As research on PPAs in organizations moves forward, we need to know both why a specific activity works (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation